Corporate Social Responsibility in Mekong Hydropower Development (Vietnamese) - West, Niki (CGIAR Challenge Program on Water and Food, 2013)
Reviews current literature on definitions of CSR, main international frameworks, criticisms, CSR in Asia, CSR in hydropower, and drivers and trends in CSR.